"Kesehatan Reproduksi untuk Semua": Perspektif Mahasiswa Kesehatan Masyarakat tentang Ketimpangan Gender dalam Akses terhadap Informasi dan Layanan Kesehatan Reproduksi Remaja di Indonesia - Herwansyah; Ayu Oktoviani; Adinda Juwita Sari; Kunlanant Senkham (Jurnal Kesehatan, 2025)
Reproductive health is a critical aspect of adolescent development, yet gender disparities persist in access to information and services, particularly in Indonesia. This study explores how Public Health students at Universitas Jambi perceive gender-based inequalities in adolescent reproductive health, aiming to understand how future health professionals interpret and respond to these challenges. A qualitative descriptive approach was employed, involving three focus group discussions with 24 undergraduate students (14 female, 10 male) who had completed relevant coursework and participated in health promotion activities. Thematic analysis revealed three key themes: gendered access and assumptions, socio-cultural and structural barriers, and institutional roles and responsibilities. Participants described how reproductive health education and services disproportionately focus on girls, with boys often excluded due to cultural norms and institutional biases. Socio-cultural taboos, shame, and fear further limited access for both genders, though in distinct ways: boys faced invisibility and judgment, while girls experienced stigma and moral scrutiny. Institutions such as schools, families, and healthcare providers were seen as both barriers and potential agents of change, often reinforcing gendered norms through selective education and biased service provision. These findings underscore the need for more inclusive and gender-equitable reproductive health education that actively engages all adolescents. Addressing these disparities requires rethinking institutional practices and cultural narratives that marginalize male adolescents while overburdening females with sole responsibility for reproductive health. By incorporating gender equity into academic and community-based health initiatives, Public Health students can be better prepared to advocate for and implement inclusive reproductive health programs.